Les fabriques de soi ? - Pergia Gkouskou-Giannakou (Communiquer)
The present review discuss the book Les fabriques de soi ? (written by Gustavo Gomez-Mejia (2016). The author shows how digital writing technologies construct the illusion of a euphoric and user-friendly personal and social universe of heterogeneous semio-technical elements.